2022
DOI: 10.3389/fonc.2022.985184
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-specific survival and metastasis in pancreatic mucinous cystadenocarcinoma: A SEER-based cohort study

Abstract: AimsThis study aimed to investigate the prognostic value of clinical features for cancer-specific survival (CSS) and metastasis in patients with pancreatic mucinous cystadenocarcinoma (MCAC). We further constructed and validated an effective nomogram to predict CSS.MethodsWe screened patients diagnosed with pancreatic MCAC from Surveillance Epidemiology and End Results (SEER) database. Kaplan-Meier curves were used to determine the CSS time. Univariate and multivariate Cox and logistic regression analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In our study, The CSS was found to be signi cantly lower in patients aged 70 years and above compared to younger patients. Similar results can be seen in previous studies [24,25]. Elderly patients often have poor physical tness, cannot tolerate treatment, and suffer from other conditions.…”
Section: Prognostic Nomogram Building and Validationsupporting
confidence: 90%
“…In our study, The CSS was found to be signi cantly lower in patients aged 70 years and above compared to younger patients. Similar results can be seen in previous studies [24,25]. Elderly patients often have poor physical tness, cannot tolerate treatment, and suffer from other conditions.…”
Section: Prognostic Nomogram Building and Validationsupporting
confidence: 90%
“…In summary, effective management of pancreatic malignant neoplasm plays a vital role in improving patient survival, reducing recurrence, and enhancing overall quality of life. [4], [5], [6]…”
Section: Introductionmentioning
confidence: 99%
“…For more detailed information, it is advisable to consult with a healthcare professional. [4] Chymotrypsin-like elastase family member 3B (CELA3B) functions as an enzyme in the pancreas associated with digestive functions. Its expression is exclusive to the pancreas, and studies have explored its potential diagnostic value in distinguishing distinguishing pancreatic from non-pancreatic cancers and within differentiating acinar cell carcinoma from adenocarcinoma of the ducts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation